2016
DOI: 10.1093/hmg/ddw081
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate filament aggregates cause mitochondrial dysmotility and increase energy demands in giant axonal neuropathy

Abstract: Intermediate filaments (IFs) are cytoskeletal polymers that extend from the nucleus to the cell membrane, giving cells their shape and form. Abnormal accumulation of IFs is involved in the pathogenesis of number neurodegenerative diseases, but none as clearly as giant axonal neuropathy (GAN), a ravaging disease caused by mutations in GAN, encoding gigaxonin. Patients display early and severe degeneration of the peripheral nervous system along with IF accumulation, but it has been difficult to link GAN mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 71 publications
3
78
0
Order By: Relevance
“…Given the previous observations that gigaxonin clears several IF proteins, including vimentin, as well as peripherin and neurofilament light chain (Mahammad et al ., 2013; Israeli et al ., 2016), we tested whether gigaxonin could clear GFAP, a type III IF protein expressed predominantly in astrocytes. Primary astrocytes were infected with a lentivirus expressing FLAG-gigaxonin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the previous observations that gigaxonin clears several IF proteins, including vimentin, as well as peripherin and neurofilament light chain (Mahammad et al ., 2013; Israeli et al ., 2016), we tested whether gigaxonin could clear GFAP, a type III IF protein expressed predominantly in astrocytes. Primary astrocytes were infected with a lentivirus expressing FLAG-gigaxonin.…”
Section: Resultsmentioning
confidence: 99%
“…The AxD-like pathology observed in GAN suggests that loss of gigaxonin also affects GFAP, causing it to accumulate and aggregate in a manner similar to its effects on other IF proteins. Although the mechanism by which loss-of-function mutations in gigaxonin interfere with the IF system is not known, recent studies suggested a functional role of gigaxonin in regulating the degradation of several IF proteins through the ubiquitin-proteasome pathway (Mahammad et al ., 2013; Opal and Goldman, 2013; Israeli et al ., 2016). In support of this role, studies of Gan −/− mice revealed pathological features similar to those found in GAN patients (Dequen et al ., 2008; Ganay et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The human ATXN1 coding sequence containing either 2 or 82 CAG repeats was subcloned from the FLAGtagged pCDNA-ATXN1 construct into the pLEX lentiviral vector using SpeI and NotI as restriction sites (58). All lentiviruses were produced as mentioned previously (59). In brief, HEK293T cells were grown in DMEM High Glucose Medium (Gibco, Thermo Fisher Scientific) supplemented with 10% FBS, 2 mM l-glutamine, 100 U/ml penicillin, and 100 μg/ml streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…While the regulation and function of gigaxonin remain incompletely understood, several lines of evidence suggest possible connections to cellular metabolism. For example, GAN-deficient cells exhibit dysregulated mitochondrial distribution and behavior (10,13). In GAN loss-of-function cells, mitochondria often co-localize with ovoid IF aggregates, frequently found near the nucleus, and mitochondrial motility is reduced (10,13).…”
Section: Giant Axonal Neuropathy (Gan)mentioning
confidence: 99%
“…For example, GAN-deficient cells exhibit dysregulated mitochondrial distribution and behavior (10,13). In GAN loss-of-function cells, mitochondria often co-localize with ovoid IF aggregates, frequently found near the nucleus, and mitochondrial motility is reduced (10,13). Although mitochondrial inner membrane potential is not affected by loss of gigaxonin function (13), the oxygen consumption rate is increased in GAN knockout, GAN knockdown and CUL3 knockdown cells (10), consistent with functional links among gigaxonin/CUL3 complexes, IFs and mitochondrial physiology.…”
Section: Giant Axonal Neuropathy (Gan)mentioning
confidence: 99%